PENGARUH KEBISINGAN DI LINGKUNGAN SEKOLAH DAN MINAT BELAJAR TERHADAP HASIL BELAJAR SISWA KELAS XI PADA MATA PELAJARAN EKONOMI DI SMA N 1 BASA AMPEK BALAI KABUPATEN. PESISIR SELATAN - Yunita, Ika - (Pendidikan Ekonomi, 2014)
This research aims to understand how the influence of noise in the vicinity of the school and interest learn of the results of the class student learning xi on the subjects of economic in high school n 1 bases ampek balai district.The southern coast of the.Methods used in this research is a method of surveying; with a population of there are 152 students and the total sample 110 students.The sample collection technique in this research are proportionate simple random sampling of study result of the students obtained from existing data at school while noise in the vicinity of the school and interest obtained from the results of the spread of kuisioner that has been tried out beforehand.The analysis used in this research was descriptive analysis and inductive analysis. This research result indicates that noise in the school in partial having negative influence and interest learning influential positive while simultaneously influential positive and significantly to study result of the graders xi on the subjects economic in sma n 1 basa ampek balai district.Southern coast. The regression r square known value r square is worth 0,703.It showed that immensity contribution given by noise in the school and interest learned to study result of the economic in sma n 1 basa ampek balai district.Coastal southern is worth 71.5 % and the rest 28.5 % determined / influenced by factors another not subjects in this study. Keyword: Noise In The School and Interest Learned To Study Result